Evaluation of the effectiveness of a general tonic feed additive for minks under industrial production conditions - Viktor N. Denisenko; Pavel N. Abramov; Nikolay A. Balakirev; Alexey I. Albulov; Marina A. Frolova (RUDN Journal of Agronomy and Animal Industries)
Feeding balanced in amino acids, micro and macro elements, vitamins and other biologically active substances is a necessary condition for the productivity and development of fur animals, as well as for obtaining high-quality fur raw materials. Analysis of the amino acid profile of the main productive diet of the mink at JSC Fur Farm Saltykovsky revealed a deficiency of the essential amino acids: histidine, tryptophan and threonine, when maintaining a total protein within the normal range. To correct protein metabolism, a hydrolysate from sable and mink carcasses after technological euthanasia and skinning was included in the diet of minks. The hydrolysate is sterile, does not have pyrogenicity, acute and chronic toxicity, does not cause allergic reactions, contains 18 amino acids, including 10 essential, 6 macronutrients (Ca, Na, S, Mg, K, P) and 18 trace elements. A scientific and economic experiment was carried out by a commission on the basis of JSC Fur Farm Saltykovsky on standard wild mink 3 months of age, of which 1 control and 2 experimental groups of 120 animals each (60 males and 60 females) were formed. The results of the experiment showed that the feed additive in doses of 2 and 4 ml of a 15% solution per capita mixed with feed of the productive diet once a day for 4 months has a tonic effect on the mink organism.